The Effect of Differentiated Instruction on EFL Students’ Reading Comprehension Viewed from Critical Thinking - Utama, I Made Permadi; Sandiarsa, K. Dedy S; Hafidz, Abdul (Journal of Language and Literature Studies, 2026)
Reading comprehension in EFL higher education remains challenging because many students struggle to engage in higher-order processes such as inference, evaluation, and interpretation of academic texts. These difficulties are often intensified by the use of uniform instructional practices that do not adequately address learner diversity. This study aimed to investigate the effect of differentiated instruction on EFL students’ reading comprehension and to examine differences based on students’ levels of critical thinking. The study employed a pre-experimental one-group pre-test–post-test design involving 40 first-year students in an English Language Education program. Data were collected through reading comprehension tests and a critical thinking assessment. The findings revealed an improvement in students’ reading comprehension after the implementation of differentiated instruction, as indicated by the increase in mean scores from the pre-test to the post-test. The paired-sample t-test showed that the improvement was statistically significant (t(39) = 28.01, p < .001). Further analysis indicated that students with higher levels of critical thinking achieved greater gains, particularly in inferential and evaluative comprehension, although students with lower critical thinking levels also demonstrated meaningful improvement. These findings suggest that differentiated instruction can support reading comprehension development while accommodating learner diversity in EFL classrooms. The study highlights the importance of aligning instructional practices with students’ cognitive characteristics to support higher-order reading processes in higher education contexts.